Whole genome sequencing identifies candidate genes for familial essential tremor and reveals biological pathways implicated in essential tremor aetiology - Lorraine N. Clark; Yizhe Gao; Gao T. Wang; Nora Hernandez; Allison Ashley-Koch; Joseph Jankovic; Ruth Ottman; Suzanne M. Leal; Sandra M. Barral Rodriguez; Elan D. Louis (EBioMedicine, 2022)
Summary: Background: Essential tremor (ET), one of the most common neurological disorders, has a phenotypically heterogeneous presentation characterized by bilateral kinetic tremor of the arms and, in some patients, tremor involving other body regions (e.g., head, voice). Genetic studies suggest that ET is genetically heterogeneous. Methods: We analyzed whole genome sequence data (WGS) generated on 104 multi-generational white families with European ancestry affected by ET. Genome-wide parametric linkage and association scans were analyzed using adjusted logistic regression models through the application of the Pseudomarker software. To investigate the additional contribution of rare variants in familial ET, we also performed an aggregate variant non-parametric linkage (NPL) analysis using the collapsed haplotype method implemented in CHP-NPL software. Findings: Parametric linkage analysis of common variants identified several loci with significant evidence of linkage (HLOD ≥3.6). Among the gene regions within the strongest ET linkage peaks were BTC (4q13.3, HLOD=4.53), N6AMT1 (21q21.3, HLOD=4.31), PCDH9 (13q21.32, HLOD=4.21), EYA1 (8q13.3, HLOD=4.04), RBFOX1 (16p13.3, HLOD=4.02), MAPT (17q21.31, HLOD=3.99) and SCARB2 (4q21.1, HLOD=3.65). CHP-NPL analysis identified fifteen additional genes with evidence of significant linkage (LOD ≥3.8). These genes include TUBB2A, VPS33B, STEAP1B, SPINK5, ZRANB1, TBC1D3C, PDPR, NPY4R, ETS2, ZNF736, SPATA21, ARL17A, PZP, BLK and CCDC94. In one ET family contributing to the linkage peak on chromosome 16p13.3, we identified a likely pathogenic heterozygous canonical splice acceptor variant in exon 2 of RBFOX1 (ENST00000547372; c.4-2A>G), that co-segregated with the ET phenotype in the family. Interpretation: Linkage and association analyses of WGS identified several novel ET candidate genes, which are implicated in four major pathways that include 1) the epidermal growth factor receptor-phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha-AKT serine/threonine kinase 1 (EGFR-PI3K-AKT) and Mitogen-activated protein Kinase 1 (ERK) pathways, 2) Reactive oxygen species (ROS) and DNA repair, 3) gamma-aminobutyric acid-ergic (GABAergic) system and 4) RNA binding and regulation of RNA processes. Our study provides evidence for a possible overlap in the genetic architecture of ET, neurological disease, cancer and aging. The genes and pathways identified can be prioritized in future genetic and functional studies. Funding: National Institutes of Health, NINDS, NS073872 (USA) and NIA AG058131(USA).